Integrated coastal zone management with a good governance approach (Kish Island case example) - Abbas Ladani; Ahmad Pour Ahmad; Karamatollah Ziyari; Rahmatollah Farhoudi; Saeed Zanganeh Shahraki (تحقیقات کاربردی علوم جغرافیایی)
The purpose of this study was to develop good governance indicators and criteria, evaluate good governance in integrated management of Kish, and provide strategies to promote integrated management of coastal areas with good governance approach. To accomplish these goals, firstly, by explaining the subject literature and reviewing the research background, an integrated coastal zone management model with a good governance approach was presented. The main criteria in this model are participation, legislation, accountability, accountability, central justice, transparency, efficiency and effectiveness, and community-centricity, each of which includes sub-criteria. Then, by using questionnaire and interviewing residents and experts, as well as by applying hierarchical analysis method, good governance status in integrated management of Kish was assessed. The final score of Kish by calculations was 2.53 (out of 5), indicating a relatively inadequate situation of good governance in Kish integrated management. Finally, solutions were presented to promote good governance in the integrated management of